Student perception of workplace‐based assessment. (December 2013) - Nesbitt, Alexander; Baird, Freya; Canning, Benjamin; Griffin, Ann; Sturrock, Alison
Summary Background Workplace‐based assessment (WPBA) is key to medical education, providing a framework through which the trainee can be assessed and receive feedback in the clinical setting. WPBA was introduced in 2008–2009 to students in year 4 at University College London Medical School (UCLMS). Students raised concerns about the lack of standardisation in grading. As a result, white‐space areas were introduced on WPBA forms. The aim of this was to permit assessors to expand their feedback, thereby enhancing its developmental potential. The aim of the project was to assess student perception of WPBA at UCLMS, and to determine whether re‐designing the form had altered this perception. Method An online survey was circulated to students in year 4 at the end of the academic year 2009–2010, and was repeated with the next cohort of year–4 students at the end of the academic year 2010–2011. Students were asked to express a level of agreement with 12 statements and for free‐text comments on their experience with WPBA. Survey responses were analysed using an unpaired two‐tailed Student's t‐test, and QSR NVivo was used to manage the thematic analysis of the free‐text comments. Results Although there was no significant difference in student perception between cohorts, the analysis of free‐text comments highlighted several themes for discussion. Conclusion Students at UCLMS find WPBA valuable in highlighting areas for improvement and obtaining personalised feedback. They find the grading of WPBA too subjective, and that the attitudes of the assessors sometimes reduce its educational value. Suggestions are made to improve the value of WPBA in undergraduate medical education.